Prevalence of infectious diseases in preterm infants: a 2-year follow-up from the Japan Environment and Children’s Study - Kentaro Tamura; Kenta Matsumura; Akiko Tsuchida; Taketoshi Yoshida; Hidekuni Inadera; The Japan Environment and Children’s Study (JECS) Group (Scientific Reports, 2022)
Abstract Evidence regarding the long-term risk of infections in preterm infants is lacking. In this study, we examined whether preterm infants developed various common childhood infections more frequently than full-term infants by the age of 2 years by analyzing data from a questionnaire completed by 67,282 mother–toddler pairs in a nationwide birth cohort study. Of the target population, 2885 (4.3%) were born prematurely. After covariate adjustment for maternal and children factors, lower respiratory tract infections appeared more frequent in preterm than in full-term infants at both 1 and 2 years (adjusted odds ratio [aOR] 1.21, 95% confidence interval [CI] 1.05–1.41, and aOR 1.27, 95% CI 1.11–1.46, respectively). However, there was no significant difference in the frequencies of lower respiratory tract infection between preterm and full-term infants after Palivizumab administration. The risk of other common infections, such as in the upper respiratory tract infection, otitis media, urinary tract infection, gastroenteritis, herpangina, hand-foot-and-mouth disease, chickenpox, influenza virus, and adenovirus infections, was not higher in preterm than in full-term infants after covariates adjustment for maternal and children factors. These findings suggest Palivizumab prophylaxis could reduce the frequencies of lower respiratory tract infection in preterm to the same level as in full-term infants.